Do the Fish Scales Shape of Mugil curema Reflect the Genetic Structure Using Microsatellites Markers and the Mexican Marine Ecoregions Classification? - Pacheco-Almanzar, Eloísa; Loza-Estrada, Nadia; Ibáñez, Ana L. (Frontiers in Marine Science, 2020)
Mugil curema is a teleost fish of economic importance that shows wide phenotypic variability in the coasts of Mexico. Intraspecific morphological variability might replicate either genetic dissimilarity between groups or environmental conditions according to phenotypic plasticity. Fish scales shape was used to discriminate location variants, genetic structure obtained by microsatellite markers, and marine ecoregions of Mexico. The present study uses landmarks and geometric morphometric statistical approaches to address the specific question: if and how fish scale shape varies with genetic structure or with marine ecoregions. This is assessed using seven landmarks by scale, the coordinates of which were subjected to a generalized Procrustes analysis, followed by a principal components analysis and quadratic discriminant analysis with cross-validation analysis on shape. Also, the significance of classifications was assessed by multivariate analysis of covariance (MANCOVA). The proportion of total shape variance explained by total length and by centroid size was 3.8 and 3.0%, respectively. Therefore, only shape (without size) was used for the analysis. MANCOVA was significant in all cases, with locations, genetic structure, and marine ecoregions. The cross-validated discriminant analysis by location correctly classified 42.2%, whereas with the genetic structure prearrangement and marine ecoregions, the identification rates were 58.3 and 57.0%, respectively. It was surprising that, as the same as in the genetic structure (microsatellite analysis), San Antonio Bay, Texas formed a group with Sabancuy, Campeche, Celestun, and Sisal, Yucatan (the Caribbean locations). Likewise, Huave Lagoon System, Oaxaca, located in the Pacific coast is more similar to the Caribbean sites unlike the other locations from the Pacific area, which are similar results depicted with microsatellite analysis. On the other hand, using the marine ecoregions arrangement, the findings indicate that the Mexican Tropical Pacific and the Chiapas-Nicaragua marine ecoregions were very different as opposed to the two marine ecoregions from the Gulf of Mexico more similar in fish scale shape. The Mexican Tropical Pacific ecoregions show more identification rate (80.4%), whereas the rest of marine ecoregions discriminate less than 53.3%. Possibly, hydrographic features as currents or upwellings circumscribe boundaries between marine ecoregions, and this could produce inherent genetic structure.